Pregunta
upstudy study bank question image url

Use the product or quotient rule or the generalized power rule to find the derivative of the function. \( y y=(6 x+5)^{6} \sqrt{x} \)

Ask by Luna Bob. in the United States
Feb 21,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The derivative of \( y = (6x + 5)^{6} \sqrt{x} \) is \( y' = \frac{(6x + 5)^{5} (78x + 5)}{2\sqrt{x}} \).

Solución

To find the derivative of the function \( y = (6x + 5)^{6} \sqrt{x} \), we will use the product rule, which states that if you have a function \( y = u \cdot v \), then the derivative \( y' \) is given by: \[ y' = u'v + uv' \] In this case, we can identify: - \( u = (6x + 5)^{6} \) - \( v = \sqrt{x} = x^{1/2} \) Next, we need to find the derivatives \( u' \) and \( v' \). 1. **Finding \( u' \)** using the chain rule: \[ u' = 6(6x + 5)^{5} \cdot (6) = 36(6x + 5)^{5} \] 2. **Finding \( v' \)**: \[ v' = \frac{1}{2} x^{-1/2} = \frac{1}{2\sqrt{x}} \] Now we can apply the product rule: \[ y' = u'v + uv' \] Substituting \( u \), \( u' \), \( v \), and \( v' \) into the product rule formula: \[ y' = 36(6x + 5)^{5} \cdot \sqrt{x} + (6x + 5)^{6} \cdot \frac{1}{2\sqrt{x}} \] Now, let's simplify this expression. The first term is: \[ 36(6x + 5)^{5} \cdot \sqrt{x} \] The second term is: \[ \frac{(6x + 5)^{6}}{2\sqrt{x}} \] To combine these terms, we can express them with a common denominator. The common denominator will be \( 2\sqrt{x} \): \[ y' = \frac{72(6x + 5)^{5} \cdot x + (6x + 5)^{6}}{2\sqrt{x}} \] Now, we can factor out \( (6x + 5)^{5} \): \[ y' = \frac{(6x + 5)^{5} (72x + (6x + 5))}{2\sqrt{x}} \] Simplifying the expression inside the parentheses: \[ 72x + 6x + 5 = 78x + 5 \] Thus, the derivative is: \[ y' = \frac{(6x + 5)^{5} (78x + 5)}{2\sqrt{x}} \] This is the final result for the derivative of the function \( y = (6x + 5)^{6} \sqrt{x} \).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To find the derivative of \( y = (6x + 5)^6 \sqrt{x} \), we can apply the product rule since we have a product of two functions: \( u = (6x + 5)^6 \) and \( v = \sqrt{x} \). We first differentiate each part: 1. \( u' = 6 \cdot 6(6x + 5)^5 \cdot 6 = 36(6x + 5)^5 \) 2. \( v' = \frac{1}{2}x^{-1/2} \) Now, using the product rule, \( y' = u'v + uv' \): - \( y' = 36(6x + 5)^5 \cdot \sqrt{x} + (6x + 5)^6 \cdot \frac{1}{2}x^{-1/2} \) To rewrite this, we can find a common form, but the derivative is best left expressed in this simplified form for clarity in steps.

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad